Research on performance evaluation of higher education based on the model of BSC-DRF-DEA - Yingxin Wu; Congdong Li (2009 IEEE 16th International Conference on Industrial Engineering and Engineering Management, 2009)
Based on the balanced scorecard (BSC) method, the performance measure indicators (PMLs) system for higher education is constructed, comprising four perspectives: financial, customer, internal process, and learning & growth. Incorporating DRF (data reduction factor) and DEA (data envelopment analysis) methods, a DRF-DEA model is proposed for university performance evaluation. The DRF approach is used to extract the rotated public factors from PML· and then DEA is applied to calculate the relative efficiency between DMUs (decision making units). The proposed DRF-DEA model can overcome the disadvantage that the differentiation of DEA's results will decrease with the increase in the number of variables. In the case study, 15 Science and Technology universities of MOE (Ministry of Education) have been chosen to illustrate the proposed model, which can evaluate the performance of higher education more scientific and reasonable.